2018
DOI: 10.3389/fnmol.2018.00269
|View full text |Cite
|
Sign up to set email alerts
|

A Loss-of-Function HCN4 Mutation Associated With Familial Benign Myoclonic Epilepsy in Infancy Causes Increased Neuronal Excitability

Abstract: HCN channels are highly expressed and functionally relevant in neurons and increasing evidence demonstrates their involvement in the etiology of human epilepsies. Among HCN isoforms, HCN4 is important in cardiac tissue, where it underlies pacemaker activity. Despite being expressed also in deep structures of the brain, mutations of this channel functionally shown to be associated with epilepsy have not been reported yet. Using Next Generation Sequencing for the screening of patients with idiopathic epilepsy, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Powell et al, 2008; Strauss et al, 2004). There is also an association between neuronal hyperexcitability and genetic change in HCN1 , HCN2 and HCN4 (Becker et al, 2017; Bonzanni et al, 2018; Campostrini et al, 2018; Dibbens et al, 2010; Marini et al, 2018; Nava et al, 2014). This relationship is complex, with evidence for both increased and decreased I h associating with heightened neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Powell et al, 2008; Strauss et al, 2004). There is also an association between neuronal hyperexcitability and genetic change in HCN1 , HCN2 and HCN4 (Becker et al, 2017; Bonzanni et al, 2018; Campostrini et al, 2018; Dibbens et al, 2010; Marini et al, 2018; Nava et al, 2014). This relationship is complex, with evidence for both increased and decreased I h associating with heightened neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed it is highly expressed in habenula and thalamus, but is low expression level in amygdala, cortex, and hippocampus, which are known ASD associated regions. (Oyrer et al, 2019;Seo et al, 2015) and a loss of function mutation in HCN4 is associated with development of infantile epilepsy (Campostrini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed it is highly expressed in habenula and thalamus, but is low expression level in amygdala, cortex, and hippocampus, which are known ASD associated regions. (Oyrer et al, ; Seo et al, 2015) and a loss of function mutation in HCN4 is associated with development of infantile epilepsy (Campostrini et al, ). ADPGK is ADP‐dependent glucokinase and an alternative, glycolytic enzyme mediating generation of the oxidative signal whose downregulation inhibits oxidative signal and induces NF‐kB‐dependent gene expression, which makes T cell activation (Kaminski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported no change in HCN4 expression in the hippocampus following febrile seizures despite changes in HCN1 (56). Loss-of-function mutations in HCN4 has also recently been associated with benign myoclonic epilepsy (57). More recently, increased HCN4 expression in the hippocampal dentate gyrus has been reported in individuals with SUDEP (58).…”
Section: Discussionmentioning
confidence: 99%